2015
DOI: 10.1200/jco.2015.60.8125
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and Asymptomatic Left Ventricular Systolic Dysfunction in Lymphoma Survivors Treated With Autologous Stem-Cell Transplantation: A National Cross-Sectional Study

Abstract: LVSD was frequent and HF more prevalent than previously reported in LSs after auto-HCT. Our results may help to identify LSs at increased LVSD risk and can serve as a basis for targeted surveillance strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 31 publications
6
55
5
Order By: Relevance
“…Cumulative anthracycline exposure was equivalent between conventionally treated and HCT survivors, and we observed no difference in echocardiographic measures of cardiac function between the 2 groups. Not surprisingly, the odds of having cardiac dysfunction in the current study (OR, 6.6) was comparable to that reported in a recent study of long-term lymphoma survivors who had undergone HCT (OR, 6.6), 9 suggesting that our findings may be broadly applicable to other populations of anthracycline-exposed lymphoma survivors, regardless of HCT status.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Cumulative anthracycline exposure was equivalent between conventionally treated and HCT survivors, and we observed no difference in echocardiographic measures of cardiac function between the 2 groups. Not surprisingly, the odds of having cardiac dysfunction in the current study (OR, 6.6) was comparable to that reported in a recent study of long-term lymphoma survivors who had undergone HCT (OR, 6.6), 9 suggesting that our findings may be broadly applicable to other populations of anthracycline-exposed lymphoma survivors, regardless of HCT status.…”
Section: Discussionsupporting
confidence: 87%
“…Until now, very little was known about the prevalence of asymptomatic cardiac dysfunction in these long‐term survivors. Recent studies have suggested that lymphoma survivors who have undergone autologous HCT may be at an especially high risk of developing symptomatic heart failure, which is attributed to additional HCT‐related conditioning chemotherapy and/or radiation exposures in this population. To our knowledge, no study has compared the prevalence of asymptomatic cardiac dysfunction in HCT survivors with that in conventionally treated patients, and few have compared the prevalence with that in the general population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four investigations relied on self‐reporting of CVD outcomes, however, all remaining studies measured the outcome objectively. Five studies did not describe the attrition of participants or had a loss‐to‐follow up greater than 20% with no description of lost participants …”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 articles included in this review, 13 (59%) originated from Europe and nine (41%) originated from North America. All studies had a cohort design, except for three, 36,49,52 that were cross-sectional studies. Thirteen studies presented standardized incidence ratios, 33,35,[37][38][39][40]42,44,47,48,50,51,54 two studies used hazard ratios, 41,46 three studies provided relative risk ratios, 34,43,45 three studies used odds ratios, 49,52,53 and one study presented a prevalence ratio.…”
Section: Study Characteristicsmentioning
confidence: 99%